Microwave engineering of ZnWO4 nanostructures: Towards morphologically favorable structures for photocatalytic activity. Issue 7 (August 2015) - Amouzegar, Z.; Naghizadeh, R.; Rezaie, H.R.; Ghahari, M.; Aminzare, M.
Abstract: Nanocrystalline ZnWO4 photocatalysts were successfully prepared by microwave-assisted-solid state metathesis, microwave-assisted-precipitation, and microwave-assisted-molten salt techniques at 250 °C. The obtained products were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), infrared (IR), photoluminescence (PL), and diffuse reflectance spectroscopy (DRS). The results showed that morphology and dimensions of the products are highly dependent upon the mixing mode of the ingredients. Nanoribbons synthesized by a microwave-assisted-solid state metathesis approach (MWASSM) has the best photocatalytic activity with RhB degradation rate of 74% after 75 min. High photocatalytic activity of MWASSM sample was due to low concentrations of hydrogen-related defects, high crystallinity, and high aspect ratio of obtained nanoribbons.